Comparative Evaluation of the Essential Oils Derived from Aromatic Waters of Three Thyme Species Cultivated in Semnan - M Ghiaci Yekta; F Khalighi-Sigaroodi; Kh Didehban; F Bahadori (Institue of Medicinal Plants, ACECR, 2019)
Background: The genus Thymus is a perennial and aromatic plant and belongs to Lamiaceae family. The essential oils of these plants are used for the treatment of mouth and throat mucosal inflammation, catarrh and respiratory disorders and as antioxidant and antiseptic. Objective: The purpose of this study was to compare chemical composition of the essential oils derived from aromatic waters of three thyme species cultivated in Semnan and to investigate the antioxidant properties of aromatic waters and the essential oils. These three species are used in manufacturing of thyme aromatic water in Iranian market. Methods: In this study, aerial parts of three cultivated species, Thymus vulgaris, Thymus daenensis and Thymus kotschyanus were collected from Semnan natural resources research field in Shahmirzad. At first, the aromatic waters of dried plants were extracted by water distillation method, and then the essential oils of the aromatic waters were isolated using pentane and analyzed by GC/MS. Then antioxidant activities of thyme waters and the derived essential oils were evaluated by DPPH radical scavenging method. Results: Thymol was the major component of the derived essential oils of two species Thymus vulgaris (38.36 %) and Thymus daenensis (56.82 %), while α-terpinyl acetate (31.06 %) was the main ingredient of the essential oil of Thymus kotschyanus. The most antioxidant activity was observed in the essential oil and aromatic water of Thymus daenensis. Conclusion: Chemical composition of the essential oils derived from aromatic water of three thyme species used in manufacturing of thyme water in Iranian market were completely different and it can affect the effectiveness of aromatic thyme water.